THE AUTHORITY AND SUPERVISION OF NAZIR IN DEVELOPMENT OF WAQF ACCORDING TO JURISPRUDENCE PROVISION ANDA INDONESION LAW NUMBER 41 OF 2004 - Cut Endang Puspa Sari (STAI Al-Washliyah Banda Aceh, 2019)
Nazir has main role to success development of waqf, therefore nazir needs the authority to fullfil his task and obligation as well which is the extended authority help nazir to fulfill his task as well to avoid unlawfull action and lead to disputes. This study aims to answer the question as follow: first, to determine the authority and supervision of nazir in development of waqf according to jurisprudence provision anda Indonesion law number 41 of 2004. This research uses descriptive and comparison analysis with type of library research to solve the problem by collecting, compiling, and clarified thought the study of literature then compares two variables that will be studied to aims the advantages and disadvantages of each variable. The result of this study is the discussion of nazir authority always mergering by his task. The authority of development waqf is given though nazir to make discussion, order, and delegating the task to the other parties, which is all this thing to develop dan proctec the waqf. Kind of this development authority such as to rent, plan land of waqf and partnership with the other parties Then kind of protecting authority such as record endowment, to claim, and prohibits the parties to the destruction dan another effort. Then about supervision of nazir under government authority, which is this is unstructured in jurisprudences provisions. In this case government assisted by judge in settlement of disputes dan also supervision of nazir. Unlike the supervison of nazir according the Indonesian law number 41 of 2004 structured and decided well under the authority ministry of religion dan waqf entity of Indonesia(BWI)